Genome-Wide Association Study Using Whole-Genome Sequencing Identifies a Genomic Region on Chromosome 6 Associated With Comb Traits in Nandan-Yao Chicken - Yang, Zhuliang; Zou, Leqin; Sun, Tiantian; Xu, Wenwen; Zeng, Linghu; Jia, Yinhai; Jiang, Jianping; Deng, Jixian; Yang, Xiurong (Frontiers in Genetics, 2021)
Comb traits have potential economic value in the breeding of indigenous chickens in China. Identifying and understanding relevant molecular markers for comb traits can be beneficial for genetic improvement. The purpose of this study was to utilize genome-wide association studies (GWAS) to detect promising loci and candidate genes related to comb traits, including comb thickness, comb weight, comb height, comb length, and comb area. Genome-wide single-nucleotide polymorphisms (SNPs) and small insertions/deletions (INDELs) in 300 Nandan-Yao chickens were detected using whole-genome sequencing. In total, we identified 134 SNPs and 25 INDELs that were strongly associated with the five comb traits. A remarkable region spanning from 29.6 to 31.4 Mb on chromosome 6 was found to be significantly associated with comb traits in both SNP- and INDEL-based GWAS. In this region, two lead SNPs (6:30,354,876 for comb weight and comb thickness, and 6:30,264,318 for comb length) and one lead INDEL (a deletion from 30,376,404 to 30,376,405 bp for comb length and comb thickness) were identified. Additionally, two genes were identified as potential candidates for comb development. The nearby gene fibroblast growth factor receptor 2 (FGFR2)—associated with epithelial cell migration and proliferation—and the gene cytochrome b5 reductase 2 (CYB5R2)—identified on chromosome 5 from INDEL-based GWAS—are significantly correlated with collagen maturation. The findings of this study could provide promising genes and biomarkers to accelerate genetic improvement of comb development based on molecular marker-assisted breeding in Nandan-Yao chickens.